2020
DOI: 10.1038/s41598-020-77213-9
|View full text |Cite
|
Sign up to set email alerts
|

In situ casting of rice husk ash in metal organic frameworks induces enhanced CO2 capture performance

Abstract: Incorporation of rice-husk-ash (RHA), an agricultural waste, in situ during the synthesis of MIL-101(Cr) resulted in a significant improvement in the CO2 adsorption properties over the synthesized RHA-MIL-101(Cr). The newly synthesized RHA-MIL-101(Cr) composite exhibited an enhancement of 14–27% in CO2 adsorption capacity as compared to MIL-101(Cr) at 25 °C and 1 bar. The content of RHA incorporated in RHA-MIL-101(Cr) fine tuned the CO2 capture performance to achieve high working capacity (0.54 mmol g−1), high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…S7a,† it can be observed that the N 2 sorption isotherm of RHA at −196 °C showed a type III isotherm, which is consistent with the mesoporous and amorphous nature of RHA. 42,43 On the other hand, MIL-101(Cr) and RHA-MIL-101(Cr) showed a type I isotherm which is a characteristic of microporous solids having relatively small external surfaces. 65 This observation is consistent with the isotherm obtained for MIL-101(Cr) 28 indicating that the framework of MIL-101(Cr) is intact even after incorporation of RHA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S7a,† it can be observed that the N 2 sorption isotherm of RHA at −196 °C showed a type III isotherm, which is consistent with the mesoporous and amorphous nature of RHA. 42,43 On the other hand, MIL-101(Cr) and RHA-MIL-101(Cr) showed a type I isotherm which is a characteristic of microporous solids having relatively small external surfaces. 65 This observation is consistent with the isotherm obtained for MIL-101(Cr) 28 indicating that the framework of MIL-101(Cr) is intact even after incorporation of RHA.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, silica-rich rice husk ash (RHA) has been used as a feedstock for developing various CO 2 capture adsorbents [40][41][42][43] owing to its amorphous/mesoporous nature and exposed silanol bonds, which can facilitate interactions with CO 2 molecules. 44,45 However, the direct utilization of RHA for synthesizing silica rich MOFs and its impact on CO 2 adsorption properties at lower pressures have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be anticipated that functionalized MOF can be one of the most powerful materials used for adsorption. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The development of MOFs has had a significant impact on various fields of chemistry and materials science. Polymer science exploited this novel type of material for various purposes, which is due to their defined porosity, high surface area, and catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption process with MOF adsorbents has been considered by many researchers due to its cost‐effectiveness, excellent efficiency and the facility of operation as one of the most effective processes used for gas or liquid phase adsorption as well as environmental compatibility. It can be anticipated that functionalized MOF can be one of the most powerful materials used for adsorption [17–30] …”
Section: Introductionmentioning
confidence: 99%